Utility of Glycosylated TIMP3 molecules: Inhibition of MMPs and TACE to improve cardiac function in rat myocardial infarct model - Chintalgattu, Vishnu (Pharmacol Res Perspect, 2018)
Tissue Inhibitor of Metalloproteinase 3 (TIMP3) is a secreted protein that has a great utility to inhibit elevated metalloproteinase (MMP) activity in injured tissues including infarcted cardiac tissue, inflamed vessels, and joint cartilages. An imbalance between TIMP3 and active MMP levels in the local tissue area may cause worsening of disease progression. To counter balance elevated MMP levels, exogenous administration of TIMP3 appeared to be beneficial in preclinical studies. However, the current form of WT‐TIMP3 molecule has a limitation to be a therapeutic candidate due to low production yield, short plasma half‐life, injection site retention, and difficulty in delivery, etc. We have engineered TIMP3 molecules by adding extra glycosylation sites or fusing with albumin, Fc, and antibody to improve pharmacokinetic properties. In general, the C‐terminal fusion of TIMP3 improved expression and production in mammalian cells and extended half‐lives dramatically 5‐20 folds. Of note, a site‐specific glycosylation at K22S/F34N resulted in a higher level of expression and better cardiac function compared to other fusion proteins in the context of left ventricle ejection fraction (LVEF) changes in a rat myocardial infarction model. It appeared that cardiac efficacy depends on a high ECM binding affinity, in which K22S/F34N and N‐TIMP3 showed a higher binding to the ECM compared to other engineered molecules. In conclusion, we found that the ECM binding and sustained residence of injected TIMP3 molecules are important for cardiac tissue localization and inhibition of adverse remodeling activity.